CLINICAL RESEARCHAssessment of myocardial function in newly diagnosed Egyptian patients with clinical and subclinical thyroid diseases - Moniem, Safa Refaat Abdel; Nagwa, A.M.A.; Negm, Hany Abdel Rahman; Yousrey, Tarek Mohamed (Archives of Medical Science, 2009)
Introduction: Hyperthyroidism is the term for overactive tissue within the thyroid gland, resulting in overproduction and thus an excess of circulating free thyroid hormones: thyroxine (T4), triiodothyronine (T3), or both. Hypothyroidism is a disease state in humans and in animals caused by insufficient production of thyroid hormone by the thyroid gland. Subclinical form of the disease occurs when there are changes in TSH levels without a change in thyroid hormone levels. The aim of this work is to assess the myocardial systolic and diastolic functions in newly diagnosed Egyptian patients suffering from hypothyroidism, either clinical or subclinical, and hyperthyroidism, either clinical or subclinical also. Material and methods: One hundred subjects participated in the study including newly diagnosed patients with clinical or subclinical hyperthyroidism, those with clinical or subclinical hypothyroidism, and a control group. For all subjects participating in the study, free thyroxin (FT4), free triiodothyronine (FT3) and thyroid stimulating hormone (TSH) were assessed using solid phase enzyme chemiluminescent immunoassay, echocardiography was done and the correlation between it and the thyroid hormone levels was estimated. Results: The results of the study revealed that the clinical form of hypothyroidism had negative chronotropic, inotropic and lusitropic effects, whereas the subclinical form had relatively less negative effects. The study also revealed that the clinical form of hyperthyroidism had a positive chronotropic effect, negative lusitropic effect and significant increase in systolic blood pressure with mild left ventricular hypertrophy, whereas the subclinical form had the same effects but in a less significant pattern. Conclusions: The conclusion of the study is that the clinical forms of thyroid diseases had an effect on the myocardial functions but the subclinical forms of thyroid diseases had less significant effects and so the early treatment of thyroid diseases even in the subclinical cases has a protective effect on the myocardial functions.